The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41467-023-36439-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and microenvironmental heterogeneity shaping epithelial-to-mesenchymal trajectories in cancer

Abstract: The epithelial to mesenchymal transition (EMT) is a key cellular process underlying cancer progression, with multiple intermediate states whose molecular hallmarks remain poorly characterised. To fill this gap, we present a method to robustly evaluate EMT transformation in individual tumours based on transcriptomic signals. We apply this approach to explore EMT trajectories in 7180 tumours of epithelial origin and identify three macro-states with prognostic and therapeutic value, attributable to epithelial, hy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 100 publications
0
20
0
Order By: Relevance
“…We uncovered heterogeneous relationships across breast tissue slides with other key immune cells such as NK cells, NKT cells and T cells, highlighting the multifaceted interplay between these components. T-cells have been shown to induce EMT in breast cancer 67,68 , and this relationship has further been highlighted in bulk transcriptomics 69 and smaller scale spatial transcriptomic analyses 34,70 however there is also evidence showing the exclusion of these cells, linked to the relationship between EMT, macrophages and CAFs promoting an immune suppressed environment 64,51,71 . Indeed, our findings uncover notable associations between EMT hotspots and immune suppression, alongside signatures indicative of a response to checkpoint therapy, building upon evidence that EMT may offer crucial insights for existing strategies in immunotherapy 72,11 .…”
Section: Discussionmentioning
confidence: 94%
“…We uncovered heterogeneous relationships across breast tissue slides with other key immune cells such as NK cells, NKT cells and T cells, highlighting the multifaceted interplay between these components. T-cells have been shown to induce EMT in breast cancer 67,68 , and this relationship has further been highlighted in bulk transcriptomics 69 and smaller scale spatial transcriptomic analyses 34,70 however there is also evidence showing the exclusion of these cells, linked to the relationship between EMT, macrophages and CAFs promoting an immune suppressed environment 64,51,71 . Indeed, our findings uncover notable associations between EMT hotspots and immune suppression, alongside signatures indicative of a response to checkpoint therapy, building upon evidence that EMT may offer crucial insights for existing strategies in immunotherapy 72,11 .…”
Section: Discussionmentioning
confidence: 94%
“…Complementarily, we here show that JUNB/AP1 acts as a counterpart to promote a favorable CLA phenotypic identity in PDAC. Of note, JUNB/AP1-mediated transcriptional programs can also confer tumor-promoting functions in other cancer types [39][40][41] ; JUN/AP1 TFs are highly context dependent and may co-operate for target gene transcription [41][42][43] or oppose one another 44 Altogether, this string of insights provides a potential mechanistic foundation for several recent studies that showed a high degree of heterogeneity in the neoplastic and stromal immune compartments in human PDAC, including hybrid/intermediate/coexpressor CLA/BL subtype states that exist in naive and therapy-treated PDAC tumors [10][11][12][13][14][15][16]20,36,37 . We propose that extrinsic regional TNF-α plays an essential role in destabilizing CLA neoplastic cell identity by promoting BL cJUN/AP1-mediated transcriptional programs.…”
Section: Discussionmentioning
confidence: 96%
“…Here, we investigated the role of neoplastic AP1-mediated epigenetic and transcriptional programs in shaping the local inflammatory TiME, which in turn is critical for intratumoral subtype plasticity and PDAC aggressiveness [10][11][12][13][14][15]20,36,37 . We report that AP1 transcription factors (JUNB/AP1 vs. cJUN/AP1) hold a dichotomous role in maintaining both the plasticity and stability of CLA and BL neoplastic cells via intrinsic epigenetic and transcriptional regulation of lineage gene expression as well as extrinsic inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT can be tracked with transcriptomic methods, which are costly and don't integrate all parameters, including the morphological aspect or single-cell variation. [13] Each cell, even in homogenous condition, can be modified or modify itself from its population. [14] Single cell variation is a necessity in organism, but also a major issue when it comes to treatment, especially in highly heterogeneous malignancy like ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%